Steroids prevent early recurrence of atrial fibrillation following catheter ablation: a systematic review and meta-analysis. Issue 5 (17th October 2018) - Lei, Ming; Gong, Mengqi; Bazoukis, George; Letsas, Konstantinos P.; Korantzopoulos, Panagiotis; Li, Guangping; Bisleri, Gianluigi; Glover, Benedict; Li, Ka Hou Christien; Tse, Gary; Baranchuk, Adrian; Liu, Tong
Abstract : Previous studies have reported that steroids may reduce the risk of atrial fibrillation (AF) recurrence after catheter ablation, but data regarding this issue have been controversial. Therefore, we conducted a meta-analysis of randomized clinical trials (RCTs) and observational studies to ascertain the association of steroids and AF recurrence after ablation. PubMed, Embase, and Cochrane online databases were searched from inception to December 2017. The primary outcome of the meta-analysis was short-term or long-term AF recurrence following a single ablation procedure with or without the use of steroids. Both fixed- and random-effects models were used to calculate the overall effect estimates. Eight studies (four RCTs and four observational studies), with a total 992 patients, were included in the present study. Our meta-analysis shows that steroid use was associated with reduced AF occurrence at 3 months (odd ratio (OR) = 0.53, 95% confidence interval (CI) = 0.31–0.90, P =0.02) and 12–14 months (OR = 0.67, 95% CI = 0.47–0.95, P =0.02) after radiofrequency (RF) catheter ablation (RFCA). No clear benefit was observed for AF recurrence at 2–3 days, 1 or 24 months of follow-up. Steroid use was associated with decreased risk of early AF recurrence 3 and 12–14 months after ablation. No clear relationship was observed for 2–3 days, 1 and 24 months of follow-up and further data are needed to clarify these results.